2020
DOI: 10.1177/1044389420923470
|View full text |Cite
|
Sign up to set email alerts
|

Enforced Separations: A Qualitative Examination of How Latinx Families Cope With Family Disruption Following the Deportation of a Parent

Abstract: During the past two decades, U.S. immigration policies have been tightened resulting in increased deportations of unauthorized persons residing in the United States. This qualitative phenomenological study is theoretically grounded in family systems theory. In-depth, semi-structured interviews were conducted with Latinx youth ( n = 8) and their remaining caregivers, specifically mothers ( n = 8) who had recently experienced the deportation of the child’s father. Findings from the analysis revealed that followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Although these stressors have existed in many immigrant communities for years, providers from this study discussed how the pandemic magnified the effects of immigration stress on mental health given that they are now compounded with a severe public health and economic crisis that has limited access to needed health care. These findings echo prior research pointing to the negative impact that immigration-related barriers have on families' health and well-being (Henderson et al, 2008;Holcomb et al, 2003;Lovato & Abrams, 2021;Rojas-Flores et al, 2017;Yoshikawa, Orozco & Gonzales, 2016;Wood 2018;).…”
Section: Offering Digital Support To Promote Service Accesssupporting
confidence: 84%
“…Although these stressors have existed in many immigrant communities for years, providers from this study discussed how the pandemic magnified the effects of immigration stress on mental health given that they are now compounded with a severe public health and economic crisis that has limited access to needed health care. These findings echo prior research pointing to the negative impact that immigration-related barriers have on families' health and well-being (Henderson et al, 2008;Holcomb et al, 2003;Lovato & Abrams, 2021;Rojas-Flores et al, 2017;Yoshikawa, Orozco & Gonzales, 2016;Wood 2018;).…”
Section: Offering Digital Support To Promote Service Accesssupporting
confidence: 84%
“…Many of the sociodemographic stressors these families already face also augment the potential for barriers to mental health care (Barragán et al, 2020; Suárez-Orozco, 2017); these disparities are even greater among those with immigrant parents (Finno-Velasquez et al, 2016; Gudiño et al, 2008; Sullivan & Rehm, 2005). Mental health disparities among the Latinx community have been linked to recent immigration enforcement and the ever-present threat of deportation (Lovato & Abrams, 2021). Latinx immigrants constitute an at-risk population who are understandably wary of situations in which they must interact with authority figures (e.g., mental health service providers) due to fears of deportation or exploitation (Finno-Velasquez et al, 2016; Vargas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This administration’s anti-immigrant sentiment was exemplified through the revocation of policies protecting immigrants (e.g., Deferred Action for Childhood Arrivals protections; U.S. Department of Homeland Security, 2017), separation of migrant children from their parents, and substantial increases in immigration-related arrests (Garcini et al, 2020; Lovato, 2019; Lovato & Abrams, 2021). These spikes in the deportation of Latinxs have largely operated with a disregard for established migratory agreements and processes (Garcini et al, 2020), engendering feelings of persecution and jeopardizing the health and wellness of Latinx families (Pew Research Center, 2018).…”
Section: Sociodemographic Risks In the Latinx Communitymentioning
confidence: 99%
“…Many Latino US-citizen children live in mixed-status families in which individuals’ immigration statuses vary (Dreby 2012 ). In total, four to six million Latino children live with at least one undocumented parent or caregiver (Asad 2020 ; Lovato and Abrams 2020 ). These children live with the daily risk of the apprehension/detainment and deportation of their parents (Kirksey and Sattin-Bajaj 2021 .…”
Section: Study Backgroundmentioning
confidence: 99%
“…Children who are separated from their parents or caregivers experience intense fear and helplessness (Shadid and Sidhu 2021 ). Research has shown that children may be traumatized by these separations, which manifests as psychological distress, internalizing problems such as anxiety/depression, post-traumatic stress, externalizing problems, and somatic issues such as changes to eating or sleep habits (Lovato and Abrams 2020 ; Perreira and Pedroza 2019 ; Ayón 2016 ; Dreby 2012 ; Barajas-Gonzalez et al 2021 ). Ongoing national debate about immigration also legitimizes anti-immigrant rhetoric and fuels discrimination against Latino immigrants, especially Mexicans, who have been branded as criminals (Capps et al 2020 ; Becerra et al 2012 ; Ayón et al 2010 ).…”
Section: Study Backgroundmentioning
confidence: 99%